The Effect of Performance-Based Compensation, Collaborative Work Environment, and Organizational Culture on Generation Z Employee Motivation in the Food and Beverage (F&B) Industry in Indonesia - Judijanto, Loso; Sofyan , Iradat Rayhan; Rustiawan , Indra; Triastuti , U. Yuyun (West Science Interdisciplinary Studies, 2025)
This study investigates the impact of performance-based compensation, a collaborative work environment, and organizational culture on the motivation of Generation Z employees in Indonesia’s food and beverage (F&B) industry. Using a quantitative approach, data were collected from 45 respondents through a structured questionnaire measured on a Likert scale (1–5). The data were analyzed using SPSS version 25, employing descriptive statistics, reliability testing, correlation analysis, and multiple linear regression. The results indicate that all three factors significantly and positively influence Generation Z employee motivation, with organizational culture having the strongest effect, followed by performance-based compensation and a collaborative work environment. These findings highlight the importance of tailored HR practices to align with Generation Z preferences, ensuring higher employee engagement, satisfaction, and retention. This study offers practical insights for F&B managers to create a motivated and high-performing workforce in a competitive industry.